PENINGKATAN KETERAMPILAN MENULIS DESKRIPSI DENGAN PENERAPAN METODE QUANTUM LEARNING PADA SISWA KELAS IV SDN JEMUR WONOSARI III/526 SURABAYA - Suprobowati Suprobowati (LPPM STAI Muhammadiyah Probolinggo, 2019)
The application of quantum learning method as a means to improve the ability to write description in fourth grade students of SDN Jemur Wonosari III/526 Surabaya . After the researchers explain about the application of quantum learning methods to teachers and their advantages, the teacher also agreed to apply the method of quantum learning in learning to write a description. Through the method of quantum learning is expected to foster interest and activity of students in learning to write a description. Such interest and interest will foster students 'enjoyment in learning that will ultimately improve students' learning abilities and learning outcomes. Therefore this research entitled